Congenital Heart Disease in East Africa - Jivanji, Salim G. M.; Lubega, Sulaiman; Reel, Bhupi; Qureshi, Shakeel A. (Frontiers in Pediatrics, 2019)
Congenital Heart Disease (CHD) is an enormous problem in Low Middle Income Countries and particularly in sub-Saharan Africa. There is an estimated 500,000 children born in Africa with CHD each year with a major proportion of this in sub-Saharan Africa. The vast majority of these children receive sub-optimal or no care at all. In East Africa: Kenya, Tanzania, and Uganda have all attempted to create a CHD service for the last 20 years with minimal success due to various factors. Visiting cardiac missions have made considerable contributions in the development of CHD services in these countries, however there remains a significant number of children with lack of care. We explore the positive aspects of the current projects, the various factors that hinder growth in this area, and what can be done to promote CHD service growth in these countries.